Adaptive potential of barley under toxic impact of cadmium in various conditions of assessment - E. V. Tovstik; O. N. Shupletsova; L. V. Panikhina; Yu. Al. Zlobina (Труды по прикладной ботанике, генетике и селекции, 2025)
Background. Determining the level of compatibility in barley (Hordeum vulgare L.) genotypes for cadmium toxicity in various test systems is important for increasing the objectivity of assessing their stress resistance. The purpose of this work was a comparative analysis of barley resistance to cadmium in laboratory and pot experiments.Materials and methods. Nine barley cultivars of various ecogeographic origin served as the material for the study. Their cadmium resistance was assessed in roll culture. The data obtained were compared with the results of the pot experiment.Results and conclusion. The toxic effect of 20 and 50 mg/dm3 Cd2+ was manifested in a decrease in the length of the roots and shoots of barley plantlets, and in the asynchrony of their growth. Barley cultivars with higher yields under cadmium stress conditions demonstrated high content of free phenolic compounds (PС) in roots and shoots, as well as the total content of PС in shoots. The relationships between the level of PС accumulation in roots and the root length index, and between PС accumulation in shoots and yield, indicated the potential value of PС in the selection of cadmium-resistant barley cultivars.